FROM TRADITIONAL TO MODERN FORMS OF CRISES – A BRIEF ANALYSIS OF HUMAN CRISES - Petrova, Elitsa Stoyanova (Annals of Spiru Haret University. Economic Series, 2023)
This article presents the variety of types of crises in human society. The reader is briefly introduced to the essence and content of the concept of crisis, as well as the concept of the human security, which emphasizes that in addition to traditional security threats, the world nowadays faces a number of modern forms of global threats. The crises caused by military conflicts; crimes against humanity; usage of weapons of mass destruction; terrorism and organized crime; natural crises and environmental degradation; economic crises and poverty; social crises; health and infectious disease crises; crises caused by globalization and by a change in the value system and morality of people; political and governance crises are presented in more detail in order to fully achieve the informative goal of the article.